A Study of Cash Management of Bangles Industries As Financial Aspects: Exploring the Cash Management Practices in Firozabad's Bangles Industry (Journal of Advances and Scholarly Researches in Allied Education, 2014)
During ancient periods, invaders brought many glass articles to India.These glass articles when rejected were collected and melted in locally madefurnace called as "Bhainsa Bhatti." This was the start of the glassindustry in Firozabad. In this furnace, wood was used as a fuel. These oldtraditional furnaces are still in use in Sasani near Aligarh and at PurdalNagar. During that time only small bottles and bangles were made. At this timeonly one bangle at a time can be made. In this bangle there was no joint. Thesebangles were called "Kadechhal Ki Chudi". Since then Firozabad is thehome of the glass industry, white and coloured glass pieces being manufacturedfor the purpose of assembling jhad and fanus (chandeliers) which were in demandby royal courts and nobles for decorating their assembling and drawing rooms.Later on phials for Itra, scents, and other cosmetic products were made. Slowlyand steadily Indian marriage items like bangles, kangans, kada, etc. wereproduced in bulk for the general public. Today it is having famous area as suhag nagar because it fulfillsalmost all the demand of bangles, kadas, kangans and other items of suhagins.Present paper is an attempt as to study of cash management of BanglesIndustries in Firozabad.